TRADITIONS AND INNOVATIONS IN MUSIC LITERATURE LESSONS (American Journal of Technology and Applied Sciences, 2026)
This article explores how to balance traditions (close listening, contextual reading, stylistic comparison, and culturally grounded interpretation) with innovations (streaming archives, interactive media, flipped learning, multimodal projects, and learning analytics) so that technology extends musical thinking rather than replacing it.